Educational Training and Services provided by the hearing-aid specialists in Spain: A comparison with the General Audiologist Model - Benitez-Barrera, Carlos R.; De Diego-Lázaro, Beatriz (Auditio, 2021)
The vocational training certificate in Hearing-Aid Specialist (HAS) was created in Spain in 2001. During this time, university programs in audiology have emerged in the form of university-specific postgraduate degrees. However, the undergraduate program in general audiology does not exist in Spain yet. The objective of this study was to examine the workplaces, services offered and the self-perceived quality of training of HAS with and without a additional university studies and to explore whether any of these professional profiles conduct activities of the "general audiologist" role that was proposed by the European Federation of Audiological Societies (EFAS). An online questionnaire was completed by 255 HAS. Analysis of variance was used to compare responses between HAS, HAS with an undergraduate degree in audiology-related discipline, HAS postgraduate qualifications in audiology, and HAS with both additional qualifications. Regardless of their level of education, most HAS indicated that they work in hearing aid centers fitting hearing aids to adult patients, for which they perceived themselves as sufficiently trained. The most educated HAS indicated working in specialized centers and providing services to pediatric patients more often. Highly educated HAS also reported a better self-perceived training on cochlear implants than HAS. In general, HAS do not receive training or offer services in areas within the competencies of the general audiologist according to the model proposed by EFAS, such as cochlear implant programming or diagnosis of vestibular disorders. Future studies focus on exploring the training received by professionals who offer this type of audiological services in Spain.